Aplicação da mineração de opinião no planejamento turístico do município de Gramado - Endres, Marco Antonio Trois (Universidade do Vale do Rio dos Sinos, 2016)
The purpose of this study is to explore the knowledge discovery process and analyze the opportunities generated by the Opinion Mining as a technique to obtain a feedback on the tourist experience about products and services offered by the tourist destination. Understanding the tourist about their buying behavior and their travel habits is essential to the expansion of the tourist market and improvement of the tourist experience. Web users have the opportunity to register and show their ideas and opinions through posts on social networks. These opinions are available in high volume to organizations. In this context, what are the contributions of Opinion Mining to generate useful information for the management of tourism activities, to support the decision-making process in planning and improvement of their actions? This study analyses the comments registered on social networks by tourists who visit Gramado/RS. To achieve the purpose of this study, opinions were extracted from Twitter and Facebook and submitted to a sentiment analysis technique. As a result of the study are presented and discussed the results summarized according to the competitiveness of dimensions that the municipality is assessed.
Keywords: Turismo; Competitividade; Mineração de opinião; Descoberta de conhecimento; Tourism; Competitiveness; Opinion mining; Knowledge data discovery; ACCNPQ::Ciências Sociais Aplicadas::Administração